Sodium metabisulfite-induced changes on testes, spermatogenesis and epididymal morphometric values in adult rats - Shahnaz Shekarforoush; Zahra Ebrahimi; Maryam Hoseini (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Sulphites are widely used as a preservative and antioxidant additives in the food and pharmaceutical industries. Many types of biological and toxicological effects of sulphites in multiple organs of mammals have been shown in previous studies. Objective: The aim of this study was to investigate the effects of sodium metabisulfite (SMB) on testicular function and morphometric values of epididymis in adult male Wistar rats. Materials and Methods: A total of 32 rats were randomly divided into four groups. The experimental groups received SMB at doses of 10 mg/kg (S10), 100mg/kg (S100), and 260 mg/kg (S260) while an equal volume of normal saline was administered to the control group via gavage. The rats were anaesthetized after 28 days and the left testis with the head of epididimis was excised following abdominal incision for histological observation using hematoxylin and eosin staining. Serum samples were collected for assay of testosterone level. The initial epididymis was analyzed for motility, morphology, and the number of sperms. Result: The results of this study showed that normal morphology, count, and motility of sperms and testosterone level were decreased in the SMB treated groups. In comparison with the control group, SMB resulted in a lower total number of spermatogonia, primary spermatocyte, spermatids, and Leydig cells. Conclusion: It is suggested that SMB decreases the sperm production and has the potential to affect the fertility adversely in male rats.